A Historical Review for City Branding: Hyper Competition, Challenges, and Improvement Opportunities - Suardi, Wahdania; Nurmandi, Achmad; Mutiarin, Dyah; Purnomo, Eko Priyo; Pribadi, Ulung; Purwaningsih, Titin; Misran; Zulkifli, Zarina; Younus, Muhammad (Jurnal Bina Praja, 2023)
This study aims to present a history of city branding: hyper-competition, challenges, and opportunities for improvement. The method used in this study used qualitative with a literature study approach. The findings in the study showed that in understanding the place and building city branding, there are at least three processes first through urban governance planning or infrastructure, then observation by looking at other places in the city branding. Finally, branding representation on social media is in the form of websites and tweets through news, while Instagram is through branding images from somewhere and several other media. Furthermore, City branding can be hyper-competition, showing that business competition is increasing. On the other hand, it can be a challenge and an opportunity considering that many cities have reimagined their competitive strategies by maximizing their internal potential, namely existing resources, to take opportunities and anticipate the threats faced. The contribution of this study provides an understanding of measurements in the city branding literature, helps researchers discover new studies, and can interpret the complex nature of cities. Another thing is that closing the gap between theory and practice presents a huge challenge for brands.